Analysis of gaseous ammonia (NH3) absorption in the visible spectrum of Jupiter - Irwin, P; Bowles, N; Braude, A; Garland, R; Calcutt, S (Elsevier, 2017)
Observations of the visible/near-infrared reflectance spectrum of Jupiter have been made with the Very Large Telescope (VLT) Multi Unit Spectroscopic Explorer (MUSE) instrument in the spectral range 0.48 – 0.93 μm in support of the NASA/Juno mission. These spectra contain spectral signatures of gaseous ammonia (NH3), whose abundance above the cloud tops can be determined if we have reliable information on its absorption spectrum. While there are a number of sources of NH3 absorption data in this spectral range, they cover small sub-ranges, which do not necessarily overlap and have been determined from a variety of sources. There is thus considerable uncertainty regarding the consistency of these different sources when modelling the reflectance of the entire visible/near-IR range. In this paper we analyse the VLT/MUSE observations of Jupiter to determine which sources of ammonia absorption data are most reliable. We find that the band model coefficients of Bowles et al. (2008) provide, in general, the best combination of reliability and wavelength coverage over the MUSE range. These band data appear consistent with ExoMOL ammonia line data of Yurchenko et al. (2011), at wavelengths where they overlap, but these latter data do not cover the ammonia absorption bands at 0.79 and 0.765 μm, which are prominent in our MUSE observations. However, we find the band data of Bowles et al. (2008) are not reliable at wavelengths less than 0.758 μm. At shorter wavelengths we find the laboratory observations of Lutz and Owen (1980) provide a good indication of the position and shape of the ammonia absorptions near 0.552 μm and 0.648 μm, but their absorption strengths appear inconsistent with the band data of Bowles et al. (2008) at longer wavelengths. Finally, we find that the line data of the 0.648 μm absorption band of Giver et al. (1975) are not suitable for modelling these data as they account for only 17% of the band absorption and cannot be extended reliably to the cold temperatures and H2/He-broadening conditions found in Jupiter’s atmosphere. This work is of significance not only for solar system planetary physics, but also for future proposed observations of Jupiter-like planets orbiting other stars, such as with NASA’s planned Wide-Field Infrared Survey Telescope (WFIRST).